2004
DOI: 10.1002/chin.200413094
|View full text |Cite
|
Sign up to set email alerts
|

New Classes of Antibacterial Oxazolidinones with C‐5, Methylene O‐Linked Heterocyclic Side Chains.

Abstract: Chains. -A series of antibacterial oxazolidinones is prepared. Structure-activity relationships are discussed and lead to the selection of the pre-clinical candidate AZD2563 (XX). -(GRAVESTOCK*, M. B.; ACTON, D. G.; BETTS, M. J.; DENNIS, M.; HATTER, G.; MCGREGOR, A.; SWAIN, M. L.; WILSON, R. G.; WOODS, L.; WOOKEY, A.; Bioorg. Med. Chem. Lett. 13 (2003) 23, 4179-4186; Chem. Infect. Discovery, AstraZeneca R&D, Waltham, MA 02451, USA; Eng.) -M. Bohle 13-094 2004 Oxazole derivatives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The history of the discovery and development of the oxazolidinone class as antibacterial agents have been previously reviewed, [79][80][81] as well as early SAR studies. [82][83][84][85][86][87][88][89][90][91][92][93][94] Oxazolidinones exert their antibacterial activity by binding to the bacterial 70S ribosome and inhibiting protein synthesis. The mechanism of this effect is unique from other classes of protein synthesis inhibitors in that they bind to the 50S ribosomal subunit, thereby preventing the binding of aminoacyl-tRNA to the peptidyl transferase center at the Asite.…”
Section: Next-generation Oxazolidinone Antibacterialsmentioning
confidence: 99%
“…The history of the discovery and development of the oxazolidinone class as antibacterial agents have been previously reviewed, [79][80][81] as well as early SAR studies. [82][83][84][85][86][87][88][89][90][91][92][93][94] Oxazolidinones exert their antibacterial activity by binding to the bacterial 70S ribosome and inhibiting protein synthesis. The mechanism of this effect is unique from other classes of protein synthesis inhibitors in that they bind to the 50S ribosomal subunit, thereby preventing the binding of aminoacyl-tRNA to the peptidyl transferase center at the Asite.…”
Section: Next-generation Oxazolidinone Antibacterialsmentioning
confidence: 99%
“…Meanwhile, further modifications of the new skeleton compound were carried out at C-5 side chain, as the reported structural modifications of oxazolidinone compounds were mainly concentrated in the C-5 side chain and the C-ring unit (30)(31)(32)(33)(34) to optimize their biological activities. It has been reported that the introduction of acetamide group (3,35,36) or triazole group (37)(38)(39)(40) at the C-5 position in oxazolidinone compounds shows good antibacterial activities; thus, acetamide group or triazole group were chosen for the derivatization of C-5 side chain. Additionally, a growing body of evidence suggests that the introduction of halogen group in the antibacterial agents could improve their biological activities (41); thus, F atom and Cl atom were introduced to some designed compound.…”
Section: Design Of Compoundsmentioning
confidence: 99%